2018
DOI: 10.4317/jced.54391
|View full text |Cite
|
Sign up to set email alerts
|

The effect of incorporating different concentrations of chlorhexidine digluconate on the degree of conversion of an experimental adhesive resin

Abstract: BackgroundThe aim of this study was to evaluate the effect of chlorhexidine digluconate incorporation on the degree of conversion of an experimental adhesive resin.Material and MethodsThe experimental resin was prepared from 70 wt% bisphenol A glycerolate dimethacrylate, 30 wt% hydroxyethyl methacrylate, silanized SiO2 nanofillers, 0.5% of camphorquinone and ethyl 4-dimethylaminebenzoate (binary photo-initiator system). Five chlorhexidine digluconate concentrations (0, 0.5, 1, 2 and 4 wt%) were then incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…As the formulation of adhesives is an industrial secret and making a new adhesive with a balanced composition takes a lot of time and study, we decided to use a commercial total-etch adhesive to formulate the adhesives with quercetin, RES, and BRP used in this research. The average values for bond strength and DC recorded in this research are in accordance with previous studies in which Single Bond 2 showed μTBS values between 31.52 MPa (1 day) and 26.15 MPa (1 year in distilled water) [59] and DC between 67.87% and 79.98% [57,59,60,61].…”
Section: Discussionsupporting
confidence: 91%
“…As the formulation of adhesives is an industrial secret and making a new adhesive with a balanced composition takes a lot of time and study, we decided to use a commercial total-etch adhesive to formulate the adhesives with quercetin, RES, and BRP used in this research. The average values for bond strength and DC recorded in this research are in accordance with previous studies in which Single Bond 2 showed μTBS values between 31.52 MPa (1 day) and 26.15 MPa (1 year in distilled water) [59] and DC between 67.87% and 79.98% [57,59,60,61].…”
Section: Discussionsupporting
confidence: 91%
“…As CHX consists of chlorine, it prevents its hydrolytic activity by binding to the zinc of the catalytic domain of MMPs [104]. When CHX digluconate (0.5 wt.%, 2.0 wt.% and 4.0 wt.%) was incorporated in experimental etch-and-rinse adhesives, no adverse effects on the degree of conversion were found [110]. However, Cadenaro et al [111] demonstrated that, although the degree of conversion was not affected by the incorporation of 1% or 5% CHX into the adhesive resins, the elastic modulus was significantly decreased.…”
Section: Strategies To Reduce Hybrid Layer (Hl) Degradationmentioning
confidence: 99%
“…Therefore, few products were proposed as cavity decontaminants with acceptable outcomes. CHX is the most employed cavity decontaminant, which has a potent antimicrobial action on dental caries, and it is capable of impeding the acquired enamel pellicle formation, thus preventing dental plaque development [ 17 ]. Moreover, maintained bond strength values were reported upon dental cavity decontamination using CHX at any assessed concentration, which could be related to its capacity to restrain matrix metalloproteinases (MMPs) responsible for adhesive interfaces degradation, thus showing enhanced bond strength outcomes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%